Quantitative Proteomics Analysis of Differentially Expressed Proteins in Serum of Former Uranium Miners by Isobaric Tags for the Relative and Absolute Quantitation. Issue 4 (13th October 2021) - Dang, Xuhong; Lin, Haipeng; Yuan, Yayi; Yang, Biao; Dong, Juancong; Zhang, Zhongxin; Yang, Kai; Li, Youchen; Li, Xiaozhen; Chai, Dongliang; Zuo, Yahui
The carcinogenicity of radon has been convincingly documented through epidemiological studies of underground miners. However, there is a lack of early warning indicators for radon radiation damage. In this study, mixed serum samples of 3 groups were collected from 27 underground uranium miners and seven aboveground miners according to the radiation exposure dose. The differentially expressed proteins in the serum were identified using the isobaric tags for the relative and absolute quantitation (iTRAQ)-based method. Some differentially expressed proteins were validated by enzyme-linked immunosorbent assay (ELISA) in 84 underground and 32 aboveground miners. A total of 25 co-differentially expressed proteins in 2 underground miner groups were screened, of which 9 were downregulated and 13 were upregulated. Biological process analysis of these proteins using Metascape showed that 5 GO terms were enriched, such as negative regulation of very-low-density lipoprotein particle clearance, endocytosis, and regulated exocytosis. The results of the ELISA for the expression levels of GCN1, CIP2A, and IGHV1-24 in the serum of 116 miners' serum showed that the levels of GCN1 and CIP2A were consistent with the iTRAQ results. In conclusion, APOC1, APOC2, APOC3, ORM1, ORM2, ANTXR1, GCN1, and CIP2A may be potential early markers of radon radiation damage.